4-phenyl-3-(pyridin-4-yl)-1H-1,2,4-triazole-5(4H)-thione - Yildirim, SÖ; Akkurt, M; Çetin, A; Cansiz, A; Sekerci, M; Kazak, C (Int Union Crystallography, 2005)
In the title compound, C13H10N4S the almost ideally planar triazole ring forms dihedral angles of 58.5 (1) and 36.9 (1)degrees with the phenyl and pyridine planes, respectively. The planes of the phenyl and pyridyl substituents form a dihedral angle of 58.5 (1)degrees with each other. The crystal packing is stabilized by intermolecular N-H...N hydrogen bonds.